2011
DOI: 10.1016/j.neuron.2011.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Plasticity of Visual Responses in the Adult Lateral Geniculate Nucleus

Abstract: SUMMARY Compared to the developing visual system, where neuronal plasticity has been well characterized at multiple levels, little is known about plasticity in the adult, particularly within subcortical structures. We made intraocular injections of 2-amino-4-phosphonobutyric acid (APB) in adult cats to block visual responses in On-center retinal ganglion cells and examined the consequences on visual responses in the lateral geniculate nucleus (LGN) of the thalamus. In contrast to current views of retinogenicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
(56 reference statements)
0
21
1
Order By: Relevance
“…The equality of transient responses to darkness and brightness is consistent with the observations of Creutzfeldt et al (18), who reported that stimuli of negative and positive contrasts elicited spike rate responses with similar response peaks, as well as similar response dynamics in "OFF" and "ON" macaque LGN cells, respectively (also see ref. 19). Our further analysis of the dark/bright asymmetry in the visually evoked LFP in layer 4C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equality of transient responses to darkness and brightness is consistent with the observations of Creutzfeldt et al (18), who reported that stimuli of negative and positive contrasts elicited spike rate responses with similar response peaks, as well as similar response dynamics in "OFF" and "ON" macaque LGN cells, respectively (also see ref. 19). Our further analysis of the dark/bright asymmetry in the visually evoked LFP in layer 4C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The stimulus consisted of a sequence of alternating black and white squares (19) ) with the background were nearly equal. Each black or white square appeared for 500 ms, and the entire sequence lasted ∼4 or ∼8 s.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, small inputs may support adult plasticity of RG connectivity through changes in synaptic weight (Litvina and Chen, 2017 ). Indeed, cat and primate TC neurons exhibit rapid plasticity in receptive field properties in response to acute perturbation of RGC or cortical input activity, as well as changes in brain state (Aguila et al, 2017; Hei et al, 2014; Moore et al, 2011). Thus the convergence of RGC inputs with varying strengths may enable plasticity of visual information transfer, which could eventually serve as a tool for correcting circuit defects secondary to development or disease.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of research is usually carried out with animals during their early postnatal life, and the plasticity has been well characterized [38,39]. A recent breakthrough in this area is the identification of a robust form of plasticity in the LGN of adult cats [40]. This study used intraocular injections of the glutamate receptor agonist to block visual responses in oncenter retinal ganglion cells and found that the inactivation led to a rapid emergence of off-center responses from on-center neurons in the LGN.…”
Section: Discussionmentioning
confidence: 99%